Design and validity of a badminton observation tool (BOT) - Valldecabres, R.; de Benito, A. M.; Casal, C. A.; Pablos, C. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2019)
Observational methodology allows analysing sports`specific behaviour context. The main purpose of this manuscriptwas to develop and validate an ad hocobservational tool for badminton singles games, which includes lunges trajectories as a non-analysed variable till this study. For that reason, the observational tool consists of 13 criteria and 47 categories mutually exclusive. 287actions of the 2015 Badminton World Championship were analysed. With the aim to assess the tool`svalidityCohen`s Kappa and generalizability theory were used. The outcomes for complete observational tool and for each criterion exceed 0.98, being above 0.81 proposed byliterature as "almost perfect".Generalizability analysis was done by two sides model (Category/Observer = C/O) and showed an excellent reliability(1.00).It could be saidthat it isa reliable tool designed for recording and analyzing the behaviourof badminton singles players.